Active substances study in fire extinguishing by water mist with potassium salt additives based on thermoanalysis and thermodynamics. (25th July 2017) - Tianwei, Zhang; Hao, Liu; Zhiyue, Han; Zhiming, Du; Yong, Wang
Highlights: The MECs of six potassium salts were tested to enriched the database of water mist. The active substances are creatively obtained by thermoanalysis experimental method. The quantitative analysis is obtained through thermodynamics method. Extinguishing occurred by water, K cations, flame radical, and other anions. Abstract: The active substances during the process of fire extinguishing by water mist with potassium salt additives was studied. The minimum extinguishing concentration (MEC) experiment results showed that K2 CO3 have the most benefit in improving the fire extinguishing efficiency of pure water with the improving rate of 37.6%, 47.2% and 64.8% which the mass percent was 1%, 2% and 5%, respectively. Other potassium salt additives followed the order by: K2 C2 O4 > CH3 COOK > KNO3 > KCl > KH2 PO4, and the reason attributed to the different active substances decomposed from flame temperature by different kinds of potassium salt additives. Thermoanalysis and characterization of the pyrolysis products of potassium salt solutions at flame temperature were analyzed through TG-DSC, XRD, and SEM, the results showed the KOH was the main product in the high extinguishing performance of potassium salts in flame chemical reactions. Thermodynamics analysis by HSC CHEMISTRY showed the K2 CO3 could provide 4.85% KOH in equilibrium substances, which well above other potassium salts, and other active substances good for fire extinguishing benefited from the intermediate product during the process of the KOH reacted with the flame free radicals.